Delegating authority to the players - An action research study of soccer coaching for elite adult players - Nikander, A. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
The goal of this research project was to plan, implement and evaluate a coaching programme for an elite adult soccer team. The study aimed at promoting a task-oriented motivation climate, especially by delegating authority to the players. Very few wider follow-up studies exist on a task oriented motivational climate being supported among elite athletes who compete in a highly ego-involving motivational climate. Method and Procedure The study is a qualitative case study and action research. The intervention lasted for eight months. The participants were 25 players of an elite adult soccer team, aged 18 - 35 years. The data collection methods were participatory observation and a diary kept by the coach (the first author). A central feature of the action research study was gradual data gathering during the implementation phase, in this case one soccer season. The data was subjected to inductive content analysis in order to produce a range of themes that would describe the events occurred. The findings were organized in a chronological order on a time-line. Four themes were found. The one reported in this paper is the level of discussions. Results The results showed that when the coach delegated authority to the players, they started to take on more responsibility in the decision making processes. The collaboration in which the players were engaged in a cognitively high-level construction of shared understanding increased during the soccer season. This was seen in the fact that, at the beginning of the season, the players did not show initiative or independent thinking in the tactical meetings or during training sessions. They did not ask many questions, their answers were short, and no topics in question were discussed in any depth. During the spring season, the amount and level of discussion improved. The players were more active and asked more questions spontaneously. Conclusions The players shared mutual and equal involvement and engagement. They became able to construct shared understanding and learning in topics involving soccer. This can be defined as a cognitively high-level discussion (Arvaja, 2005). Productive interaction, which was manifested in the cognitively high-level discussion was related to high-level understanding and learning.